2022
DOI: 10.1002/adom.202200837
|View full text |Cite
|
Sign up to set email alerts
|

Role of Octahedron Alloying in Photodynamics of Lead‐Free Halide Double Perovskite Nanoplatelets

Abstract: The lead‐free halide double perovskites have attracted great interest owing to their unique photophysical properties. Among them, the luminescence mechanisms of the Cs2AgInCl6 crystallites are still under debate. A hot‐injection method is developed to synthesize novel hollow and spatially symmetric Cs2AgInCl6 nanoplatelets (NPLs) and study the effect of the cation/octahedron alloying on their photodynamics by using the experimental characterizations in conjunction with the density functional theory calculation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 64 publications
1
6
0
Order By: Relevance
“…The imperfection often possesses right angle missing pieces, which we assign to a defective assembly and fusing process of smaller nanoplates (see Figure S15). This is in line with previous studies of self-assembled nanoplate systems. ,, …”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The imperfection often possesses right angle missing pieces, which we assign to a defective assembly and fusing process of smaller nanoplates (see Figure S15). This is in line with previous studies of self-assembled nanoplate systems. ,, …”
Section: Resultssupporting
confidence: 93%
“…This is in line with previous studies of self-assembled nanoplate systems. 24,27,50 ■ CONCLUSIONS In summary, we further study the formation of doubleperovskite Cs 2 AgBiBr 6 nanosheets. The building blocks of the nanosheets are based on advances in the colloidal synthesis of two-dimensional layered perovskites.…”
mentioning
confidence: 91%
“…[105][106][107][108][109] Through the continuous efforts, various low-dimensional perovskites have been developed, and the PLQY has been increased to over 90% in the low-dimensional metal halides perovskites. [18,26,57,59] In the low-dimensional perovskites system, their electron-phonon coupling and the structural distortion is well controlled by intentional non-ns 2 -ions doping; [110][111][112] designing suitable organic ammonium cations, [57,68,103,104] and employing external pressure compression. [68,[113][114][115] As to the lowdimensional perovskites, the bulky organic layers and inorganic layers are alternately and periodically arranged.…”
Section: Self-trapped Excitons In Lead Halide Perovskitesmentioning
confidence: 99%
“…Liu et al further pushed the QY of the nanocrystals to 68% by making sure that no Ag 0 species formed during the synthesis and by partial alloying at the B + site with K + ions (by a few percent), which slightly increased the lattice parameter and ensured a higher density of surface ligands . Morphology control appears to be another way to improve the optical properties of double perovskites at the nanoscale. Although Ma et al reported a PLQY of only 11% from Cs 2 AgInCl 6 :NaBi nanoplatelets (NPLs), , in another work Liu et al synthesized Cs 2 AgIn x Bi 1– x Cl 6 NPLs with a PLQY of 40%, much higher than that of the corresponding Bi-doped Cs 2 AgInCl 6 nanocubes (∼11%) . These promising results suggest that tuning the nanocrystal shape may represent a convenient way to optimize the PLQY.…”
mentioning
confidence: 99%